IMPROVING READING COMPREHENSION ABOUT PREPOSITION BY USING DISCUSSION METHOD AT THE EIGHT GRADE STUDENTS OF SMP SWASTA AL-WASHLIYAH SUKOHARJO MEDAN - Yenita Uswar; Riska Tiwi (Journal MELT (Medium for English Language Teaching), 2022)
The purpose of classroom action research (CAR) was to show that the discussion method can improve students' understanding of preposition learning in reading text and to what extent it can improve students' mastery of prepositions through discussion method. To analyze the data, the researcher used a percentage table. The researcher gives one pre-test before the two actions, and one post-test in one meeting. The subjects of the action research were students of class VIII SMP Swasta Al-Washliyah Sukoharjo Medan. The researcher used observation, tests (pre-test and post-test), interviews and documentation to collect data. Meanwhile, to analyze the data, the researcher used the average score of students. The results of the pre-test and post-test showed an increase in the score, as well as the KKM score for English subject who which pointed 75 as the minimum score. In the pre-test 1rd meeting, the average score was 62. Then in the 2rd meetings, the average score was 84. Cycle I in the 3rd meeting, the average score was 75.33. At fourth meetings, the average value was 85.33. Cycle II at 5rd meetings, the average value was 72.66 and 6rd meetings, the average value was 87.33. While post-test, the average value was 91.33. Based on the results above, it could be said that the discussion method could improve the students’ understanding of Prepositions.